Analisis Fundamental Laporan Keuangan pada PT Unilever Indonesia Tbk Terhadap Pengambilan Keputusan Investasi - Mukrimatin, Atikah Laili; Khabibah, Nibras Anny (Institut Bisnis dan Informatika Kesatuan, 2021)
The purpose of this study was to evaluate investment choices by analyzing PT Unilever Indonesia Tbk's financial statements for the 2016-2020 period using the Price Earnings Ratio (PER) methods. Fundamental analysis was used to determine intrinsic value in the context of an investment decision using financial indicators such as Return on Equity (ROE), Dividend Payout Ratio (DPR), Earnings per Share (EPS), Dividend per Share (DPS), and Price Earnings Ratio (EPS). The data was obtained using secondary data from PT Unilever Indonesia Tbk's annual report for the period 2016-2020. The results of this study suggest that, based on the analysis of the intrinsic value of the Q2 2021 market price, PT Unilever Indonesia Tbk is an undervalued stock, and that investment decisions should be made by purchasing shares.